Manajemen Risiko Proyek Pembangunan Gedung Perkuliahan dengan Metode Severity Index - Situmorang, Raftonado; Arsyad, Muhammad; Sari, Oryza Lhara; Saputra, Andika Ade Indra (Jurnal Proyek Teknik Sipil, 2025)
The construction projects for Buildings C and D were delayed in construction process due to financial constraints in completing building construction and the project was re-implemented so that the two buildings were classified as Construction in Progress. Efforts are made to avoid obstacles by carrying out effective risk management. Therefore, all projects require proper risk management. On the basis of these events, risk management is carried out with the aim of knowing the risks that may occur, knowing the level of risk, and knowing the dominant risk response in the construction project of Buildings C and D of the Kalimantan Institute of Technology. The method in this study uses Severity Index method in analyzing risk variables with the Guttman scale used to determine the relevance of a risk variable. Then do an analysis of the response to the dominant risk. In the correlation test, 40 indicators were found that were relevant and 4 that were irrelevant. The validity test shows 7 invalid indicators. The results obtained are 6 indicators of risk that are dominant to the value of the likelihood and impact matrix labelled "high" risk. The risk response in this study is to seek supervision of the budget specified in the contract, carry out reliable material estimation calculations, the procurement department is required to identify places for replacement materials, make re-engineering arrangements for work execution sequences, and depend on professional distributors and forwarders, ensuring experienced project employees, working drawings have clear information, and prioritizing outdoor work.